AngioVac suction embolectomy using a roller pump: Operative technique. Issue 10 (26th July 2021) - Shang, Michael; Rajabipour, Touraj; Vallabhajosyula, Prashanth
Abstract: AngioVac suction embolectomy is recommended by the manufacturer to be performed with a centrifugal pump due to safety considerations. However, roller head pumps are significantly cheaper to use, and thus may be more readily available during shortages and in resource‐poor settings. We present the technique of Angiovac suction embolectomy being successfully performed with a roller pump to evacuate a clot‐in‐transit in the inferior vena cava and right atrium, along with discussion of important safety caveats.